Two cases with chloroquine and hydroxychloroquine maculopathy - (:unkn) unknown (My University, 2011)
İki antimalarial ilaç kullanımına bağlı retinopati olgusu sunduk ve antimalarial tedavisinde tarama yöntemlerini değerlendirdik. Retina bölümümüzde takip edilen iki olgunun klinik kayıtları, fundus fotoğrafları, görme alanı, flöresan anjiografileri incelendi. İlk olguda testler yapılmış olduğu halde sonuçlarının yanlış yorumlanması, ikinci olguda ise hastaya tarama testlerinin öneminin yeterince anlatılmamış olması sebep olarak görüldü.

We described two cases of retinopathy due to antimalarial drugs and evaluated drug screening methods in antimalarial treatment. We reviewed our clinical records, fundus photographs, visual fields and the fluorescein angiographies of two patients from our retina referral department. The first case arose due to the misinterpretation of test results, despite the presence of adequate screening tests. The second case arose because of the inadequate information about the importance of screening tests.
Klorokin ve hidroksiklorokin makülopatili iki olgu
Keywords: Genel ve Dahili Tıp